2011
DOI: 10.4049/jimmunol.1101731
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor γ Is Required for CD4+ T Cell-Mediated Lymphopenia-Associated Autoimmunity

Abstract: The nuclear hormone receptor PPARγ has been shown to play an immuno-regulatory role in many immune-related cell types and activation of PPARγ has been reported to be an effective therapeutic approach in murine and human autoimmune disease. However, despite an association between lymphopenia and autoimmunity, there have been no prior studies of the role of T cell PPARγ in lymphopenia-associated autoimmunity. In the present studies we examined the role of PPARγ in CD4+ T cells in two murine models of lymphopenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Recent studies have more precisely analyzed the function of PPARγ in CD4 T-cell-targeted PPARγ-deficient mice. Expression of IL-7Rα, which is important for survival and homeostatic proliferation, in PPARγ-deficient CD4 + T cells was slightly diminished in a lymphopenic autoimmunity model, possibly suggesting a prosurvival effect in T cells (Housley et al, 2011).…”
Section: Ppars In T Cells and Autoimmunitymentioning
confidence: 98%
“…Recent studies have more precisely analyzed the function of PPARγ in CD4 T-cell-targeted PPARγ-deficient mice. Expression of IL-7Rα, which is important for survival and homeostatic proliferation, in PPARγ-deficient CD4 + T cells was slightly diminished in a lymphopenic autoimmunity model, possibly suggesting a prosurvival effect in T cells (Housley et al, 2011).…”
Section: Ppars In T Cells and Autoimmunitymentioning
confidence: 98%
“…Other groups showed a critical role for PPARγ in naturally occurring regulatory T cells (nTreg) and adipose tissue resident Treg cell function29. Despite the many anti-inflammatory effects of PPARγ, Pparg deficient CD4 + T cells lack the ability to induce systemic autoimmunity following adoptive transfer into a lymphopenic host30. Therefore, the overall biological significance of PPARγ in T-cell function is controversial, and the role of PPARγ in the regulation of fatty acid metabolism in CD4 + T cells is unknown.…”
mentioning
confidence: 99%
“…One recent paper reported that PPARγ is required for the development of autoimmunity in lymphopenic conditions due to increased apoptosis with reduced IL-7Rα expression of CD4-PPARγ KO T cells19, while there is a controversial result from previous studies showing that PPARγ is a negative regulator of T cell activation. It was reported that the transfer of PPARγ-deficient effector T cells into RAG-knockout mice showed a robust induction of colitis17.…”
Section: Discussionmentioning
confidence: 99%